Hubungan gambaran ultrasonografi ginjal dengan laju Filtrasi Glomerulus (GFR) pada penderita gangguan ginjal - Majdawati, Ana (Jurnal Kedokteran YARSI, 2009)
The aim of this research was to understand the correlation betwen renal ultrasonography examination and Glomerular Filtration Rate (GFR) in renal diseases patients that were referred to renal ultrasonografi at Radiology instalation, Sardjito Hospital. The subjects were patients with renal disorders treated from July 2008 until July 2009 that were fit to inclusion and exclusion criteria. The inclusion criteria were age 20-65 years old, normal body weight (Body Mass Index 18,5-22,9 kg/m ), and normal serum creatinin. The exclusion criteria were patients with renal congenital anomali and renal trauma. The independent variables were size, echostructure, borderline betwen cortex and medulla, pyelocaliceal system and another abnormal image such as stone, mass. The dependent variable was GFR (Schwartz). Chi square was employed to analyze correlation betwen independent and dependent variables. The result showed that significant correlation was observed between renal function (GFR) to size (p= 0,012); echostructure (p=0,000); cortex-medulla border (p= 0,004) and pyelocaliceal system (p= 0,01). On the other hand, renal stone and mass showed no corelation to renal function (GFR), p=0,670. It was suggested that further studies were still required to increase the accuracy of renal ultrasonography in clarifying the correlation between renal function to renal artery resistive index by using doppler ultrasonography.